A Novel Synthesis of N-Sulfonylformamidines from N-Sulfonylsulfonamides - Jeong, Yuri; Ban, Jaeyoung; Lim, Minkyung; Rhee, Hakjune (Synthesis, 2018)
N-Sulfonylformamidines were synthesized from N-sulfonylsulfonamides by reacting with p-toluenesulfonyl chloride (TsCl) and N,N-disubstituted formamides. In this reaction, it was expected that mixing TsCl with the N,N-disubstituted formamide would generate an iminium salt (Vilsmeier reagent). The reaction avoids the use of metal catalysts and hazardous reagents, and the desired N-sulfonylformamidines were obtained in 60% to quantitative yields.
Keywords: N-sulfonylformamidine; N-sulfonylsulfonamide; sulfonamide; sulfonyl chloride; Vilsmeier reagent